Peirce's Semiotic Representation: Synergy of Da’wa and Culture on Local Television / Representasi Semiotika Peirce: Sinergisitas Dakwah dan Budaya pada Televisi Lokal - Armiah, Armiah; hasanah, risqiatul; Falikhah, Nur (UIN Antasari Banjarmasin, 2025)
Culture is one of the broadcast programs that attract media actors, especially television. The plus value of culture increases, when the media is able to read the wishes of its target audience. Where, Urang Banjar's religious character, who likes to attend taklim assemblies to listen to the tausiah of master teachers, periodically becomes the target of the program set by Duta Tv. In research based on the semiotic approach of signs from Pierce, examined found various forms of icons, indexes and symbols from banjar culture, which were packaged by hosts with resource persons (tuan guru) in Islamic shows. As a local television, Duta Tv is able to re-present (re-presentation) the content of local wisdom of Banjar culture that touches the real life side of its community, wrapped in Islamic values. In addition, Duta Tv carefully chooses the right source with the expectations of his audience, namely an Islamic figure who is thick with his banjar language and dialect. Through the findings of research, Islamic shows on Duta tv have been able to combine local wisdom that has a positive impact on the preservation of Banjar culture and Islam.